1988
DOI: 10.1073/pnas.85.19.7251
|View full text |Cite
|
Sign up to set email alerts
|

Growth regulation of cancer metastases by their host organ.

Abstract: We analyzed mechanisms responsible for organ-specific metastasis by using two melanoma sublines derived from the same mouse tumor, of which one colonizes the lungs (Flo) and the other colonizes the liver (L8) after intravenous injection. Both lines were obtained by selective growth in lung or liver after injection of tumor cells into a tail vein or portal vein. Contrary to common concepts, the cells of the liver-colonizing melanoma line do not accumulate preferentially in the liver after intravenous administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Others have also found that lung-conditioned medium [ 1 1 ,I 21 or lung extracts [ 131 preferentially enhanced the growth of lung-metastasizing cell lines. Enhancement of the growth of metastatic cells was also observed when such cells were in contact with cells from the target organ [14]. Here we report on the purification and some of the properties of a growth factor from porcine and rat lung-conditioned medium that differentially stimulates the growth of lung-metastasizing tumor cells.…”
mentioning
confidence: 88%
“…Others have also found that lung-conditioned medium [ 1 1 ,I 21 or lung extracts [ 131 preferentially enhanced the growth of lung-metastasizing cell lines. Enhancement of the growth of metastatic cells was also observed when such cells were in contact with cells from the target organ [14]. Here we report on the purification and some of the properties of a growth factor from porcine and rat lung-conditioned medium that differentially stimulates the growth of lung-metastasizing tumor cells.…”
mentioning
confidence: 88%
“…The more tumor cells delivered to an organ, the more likely it is that metastases will result. That other factors are also involved in organ selective metastasis is clear, since metastases form in ectopic tissues in a specific manner (Kinsey, 1960;Hart and Fidler, 1980) and tumors transplanted into identical sites metastasize to different sites (Sugarbaker, 1952;Nicolson et al, 1978;Tao et al, 1979;Barnett and Eccles, 1984;Shearman and Longenecker, 1981;Brodt, 1986;Murphy et al, 1988;Chan et al, 1988;Sargent et al, 1988).…”
mentioning
confidence: 96%
“…Melanoma cells were plated with the hepatocytes at a ratio 1:100, and 6 h later HGF/SF was added at 50 ng/ ml. Four days later cells were pulse-labelled for 2 h with 1 ÌCi/ml of 3 H-bromodeoxyuridine (Amersham, specific activity 37 Ci/mmol), and processed to measure the incorporated radioactivity [5,6]. The amount taken up by melanoma cells in coculture with hepatocytes was determined after subtraction of radioactivity incorporated by hepatocytes alone under the same culture conditions.…”
Section: Hepatocytes and Organ Perfusatesmentioning
confidence: 99%
“…To this purpose, we have selected in vivo a B16 melanoma cell line (B16-LS9), showing an increased ability to colonize the liver of syngeneic mice [5]. Neither specific adhesion, nor increased retention in the liver could explain the liver specificity, which appeared rather to rely on paracrine growth effects [5][6][7].…”
Section: Introductionmentioning
confidence: 99%